2006
DOI: 10.1080/01421590600726961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teaching context and tutor workshop on tutorial skills

Abstract: Effective faculty development workshops are essential to develop and sustain the quality of faculty's teaching. In an integrated problem-based curriculum, tutors expressed the needs to further develop their skills in facilitating students' content learning and small-group functioning. Based on the authors' prior observations that tutors' performance depends on their teaching context, a workshop was designed not only tailored to the tutors' needs but also organized within their respective teaching unit. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
3
27
0
3
Order By: Relevance
“…The outcomes of these two parts are described in another paper (Baroffio et al, 2006). A third part, lasting about one hour, consisted of a brief intervention on different aspects of giving feedback.…”
Section: Teaching Intervention On Giving Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of these two parts are described in another paper (Baroffio et al, 2006). A third part, lasting about one hour, consisted of a brief intervention on different aspects of giving feedback.…”
Section: Teaching Intervention On Giving Feedbackmentioning
confidence: 99%
“…Second, we tested whether a more specific formulation of our evaluation item, might enable students to better recognize feedback when received (hypothesis b). Finally, we explored the relative importance of the tutors' teaching units that may influence students' ratings of tutors (Baroffio et al, 2006) (hypothesis c). We found that tutors rated as effective by students on year 1 improved after the teaching intervention, while those rated as unsatisfactory did not progress.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, Baroffio et al 42 demonstraram que estraté-gias de desenvolvimento docente com foco nas necessidades e dificuldades identificadas pelos tutores foram capazes de melhorar os escores de desempenho de docentes mesmo a longo prazo, principalmente para aqueles com escores pré-instrucionais mais baixos. Em estudo posterior, analisando a habilidade em oferta de feedback, Baroffio et al 43 confirmaram os efeitos benéficos do treinamento na melhora do desempenho dos tutores, ressaltando outros componentes importantes, como a clareza de critérios utilizados nos instrumentos de avaliação.…”
unclassified
“…Litzelman et al 14 found that teachers with low learner baseline ratings showed poor improvement in teaching performance after receiving feedback, compared to teachers with high baseline ratings. In contrast, Baroffio et al 15 found that a faculty development workshop for instructors teaching practice-based learning and improvement had a greater effect on teachers with low baseline scores.…”
Section: Introductionmentioning
confidence: 93%